The influence of depression on quality of life in patients with chronic heart failure - O. M. Drapkina; V. A. Dadaeva (Сеченовский вестник)
Background: chronic heart failure (CHF) is known to profoundly aff ect health related quality of life (HRQoL). Methods: 68 patients aged 43-80 years (mean duration of disease 8,63±4,52 years) were included. HRQoL was measured with the Minnesota Living With Heart Failure Questionnaire; depression — using Beck Depression Inventory. Results: depression was diagnosed in 54,4% patients with CHF. Depressive symptoms correlated with such measures of HRQoL as physical activity, social activity and psychoemotional status. Conclusion: patients with CHF suff er from severe limitations of HRQoL. Depression was the most important correlate of HRQoL.